Right-Wing Populist Party Organisation Across Europe: The Survival of the Mass-Party? Conclusion to the Thematic Issue - van Kessel, Stijn (2021)
This article provides a comparative conclusion to the thematic issue on the organisational characteristics of 12 right-wing populist parties (RWPPs) across Europe. We observe that many RWPPs—at least partially—adopt features of the mass party model. This finding illustrates the ideological aspects behind organisational choices: For populist parties, in particular, it is important to signal societal rootedness and “closeness to the people.” It furthermore challenges the idea that there is a one-way teleological movement towards more lean, electoral-professional kinds of party organisation. At the same time, the case studies clearly illustrate that RWPP leaders and executives continue to exercise great power over their members, who are essentially offered “participation without power.”